Thermal Diffusivity of Zinc Aluminum – Layered Double Hydroxide Using Photoflash Technique - Ghaziean, Maryam Ranjbar (2009)
Thermal diffusivity of zinc aluminum layered double hydroxide (Zn-Al-LDH) was measured by using photoflash technique. It used a simple camera flash and polyvinlidene diflouride (PVDF) film as signal generating source and detector respectively. Three series of sample were prepared at pH 7, 8 and 10 and with molar ratios of Zn to Al in a range from 2 to 6 (Zn/Al = 2, 3, 4, 5 and 6). The ZnO peaks appeared in x-ray diffraction pattern for all samples except for samples prepared at pH 7 with ratio 2 and 3 (Zn/Al = 2 and 3) and sample prepared at pH 8 with ratio 4. The ZnO peaks observed were between 2 = 30° to 2 = 37°. Thermal diffusivity for all three series samples (pHs 7, 8 and 10) was measured at room temperature. The thermal diffusivity for all three series of samples was found to increase for the case of molar ratio 2 to 6. The thermal diffusivity for Zn-Al-LDH at different ratios of Zn-Al-LDH increased with increasing ratio of Zn to Al. The increasing of thermal diffusivity is due to increasing of ZnO. Thermal diffusivity at pH 7, increased from 0.15 10−6m2 / s × to 0.22 10−6m2 / s × . Thermal diffusivity of sample prepared at pH 8 increased from 0.16 10−6m2 / s × to 0.20 10−6m2 / s × while at pH 10, if increased from 0.20 10−6m2 / s × to 0.25 10−6m2 / s × . Thermal diffusivity at pH 7 has the lowest value and at pH 10 has the highest value. The sample prepared at pH 7 with ratio 4 (Zn/Al = 4) was heat-treated at different temperature from 200°C to 600°C, prior to thermal diffusivity measurement at room temperature. In the case of heat treated samples, the thermal diffusivity increased from 0.25 10−6m2 / s × to 0.40 10−6m2 / s × with increasing treatment temperature.